Aqueous Chemical Solution Deposition of Functional Double Perovskite Epitaxial Thin Films. Issue 42 (11th May 2020) - Wang, Hailin; Frontera, Carlos; Herrero‐Martín, Javier; Pomar, Alberto; Roura, Pere; Martínez, Benjamín; Mestres, Narcis
Abstract: Double perovskite structure (A2 BB′O6 ) oxides exhibit a breadth of multifunctional properties with a huge potential range of applications in fields as diverse as spintronics, magneto‐optic devices, or catalysis, and most of these applications require the use of thin films and heterostructures. Chemical solution deposition techniques are appearing as a very promising methodology to achieve epitaxial oxide thin films combining high performance with high throughput and low cost. In addition, the physical properties of these materials are strongly dependent on the ordered arrangement of cations in the double perovskite structure. Thus, promoting spontaneous cationic ordering has become a relevant issue. In this work, our recent achievements by using polymer‐assisted deposition (PAD) of environmentally friendly, water‐based solutions for the growth of epitaxial ferromagnetic insulating double perovskite La2 CoMnO6 and La2 NiMnO6 thin films on SrTiO3 and LaAlO3 single‐crystal substrates are presented. It is shown that the particular crystallization and growth process conditions of PAD (very slow rate, close to thermodynamic equilibrium conditions) promote high crystallinity and quality of the films, as well as favors spontaneous B‐site cationic ordering. Abstract : Slow films : The use of polymers to control the growth of ceramic thin films can make it easier to produce materials for spintronic applications, which use electron spin instead of charge to carry information. Water‐soluble polymers bind to metal cations and slow down crystallization rates so that the most thermodynamically favored double perovskite structure films, with an optimal orientation and high magnetism for device applications, are formed.